2016
DOI: 10.1016/j.jneuroim.2015.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathology of Japanese macaque encephalomyelitis is similar to multiple sclerosis

Abstract: Japanese macaque encephalomyelitis (JME) is an inflammatory demyelinating disease that occurs spontaneously in a colony of Japanese macaques (JM) at the Oregon National Primate Research Center. Animals with JME display clinical signs resembling multiple sclerosis (MS), and magnetic resonance imaging reveals multiple T2-weighted hyperintensities and gadolinium-enhancing lesions in the central nervous system (CNS). Here we undertook studies to determine if JME possesses features of an immune-mediated disease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 51 publications
(58 reference statements)
1
20
0
1
Order By: Relevance
“…Viral genomic characterization revealed that JMERV is a gamma-2 herpesvirus closely related to rhesus macaque rhadinovirus and human herpesvirus 8 [57]. Immunopathological analysis documented the presence of several key signatures associated with MS, such as CNS-infiltrating T cells with Th1 and Th17 phenotypes besides MRI similarities, suggesting a potential use as an MS model [58].…”
Section: Japanese Macaque Encephalomyelitis Rhadinovirus (Jmerv)mentioning
confidence: 99%
“…Viral genomic characterization revealed that JMERV is a gamma-2 herpesvirus closely related to rhesus macaque rhadinovirus and human herpesvirus 8 [57]. Immunopathological analysis documented the presence of several key signatures associated with MS, such as CNS-infiltrating T cells with Th1 and Th17 phenotypes besides MRI similarities, suggesting a potential use as an MS model [58].…”
Section: Japanese Macaque Encephalomyelitis Rhadinovirus (Jmerv)mentioning
confidence: 99%
“…Tiene similitudes clínicas, de resonancia magnética y patológicas con la EM, aunque también presenta ciertas diferencias como son la cantidad de neutrófilos y linfocitos en LCR, así como necrosis y hemorragias como parte de la patología. Las lesiones observadas en estos animales son tanto agudas como crónicas 40,41 .…”
Section: Modelos De Enfermedades Desmielinizantes Viralesunclassified
“…Yellow fever virus was isolated in rhesus macaques and the subsequent development of an effective vaccine heavily relied on the use of the same experimental model (1). The immunological similarity between humans and NHP is also the basis for their use as models for infectious and autoimmune diseases (3)(4)(5). The immunological similarity between humans and NHP is also the basis for their use as models for infectious and autoimmune diseases (3)(4)(5).…”
mentioning
confidence: 99%
“…The similar manifestations of tuberculosis disease in humans and monkeys were the ground for the use of this model for vaccine and drug regimens development (2). The immunological similarity between humans and NHP is also the basis for their use as models for infectious and autoimmune diseases (3)(4)(5). More recently, a clear description of HIV-1 pathogenesis was obtained by the use of NHP models (6).…”
mentioning
confidence: 99%